Fill the Valley. Proposal for a Chronology of transfers (1959-1983) - Tormo Benavent, David; Solé Barjau, Queralt (Hispania Nova, 2023)
For more than two decades, the Valle de los Caídos was the destination of thousands of bodies transferred from cemeteries and mass graves scattered throughout the Spanish geography. Despite its continuity, it was not a uniform process. This research proposes a first chronology based on the documentation generated by the bodies responsible for the management of the monument and the transfers. Based on the existing data, the origin of the bodies, the type of transfers based on their format (individualized or in collective urns) and the volume of shipments are analysed, as well as the data related to their identification and the cause of death that attest to the difficulties that the regime had to overcome, and the strategies that it was forced to develop, in order to fill the mausolem projected by the dictator.
Keywords: Valle de los Caídos; francoism; exhumations; mass graves; chronology